Fandui baquan zhuyi, weihu shijie heping - jianchi duli zizhude duiwai zhengce - Zhang Zhaonian,
'Oppose hegemonism, uphold world peace - maintain a foreign policy of independence and own initiative'. Printno. 8073.10274.